Role of heterotrophic nitrifiers and aerobic denitrifiers in simultaneous nitrification and denitrification process: a nonconventional nitrogen removal pathway in wastewater treatment. (1st February 2022) - Gupta, R.K.; Poddar, B.J.; Nakhate, S.P.; Chavan, A.R.; Singh, A.K.; Purohit, H.J.; Khardenavis, A.A.
Abstract: Bacterial species capable of performing both nitrification and denitrification in a single vessel under similar conditions have gained significance in the wastewater treatment scenario considering their unique character of performing the above reactions under heterotrophic and aerobic conditions respectively. Such a novel strategy often referred to as simultaneous nitrification and denitrification (SND) has a tremendous potential in dealing with various wastewaters having low C : N content, considering that the process needs very little or no external carbon source and oxygen supply thus adding to its cost‐effective and environmentally friendly nature. Though like other micro‐organisms, heterotrophic nitrifiers and aerobic denitrifiers convert inorganic or organic nitrogen‐containing substances into harmless dinitrogen gas in the wastewater, their ecophysiological role in the global nitrogen cycle is still not fully understood. Attempts to highlight the role played by the heterotrophic nitrifiers and aerobic denitrifiers in dealing with nitrogen pollution under various environmental operating conditions will help in developing a mechanistic understanding of the SND process to address the issues faced by the traditional methods of aerobic autotrophic nitrification–anaerobic heterotrophic denitrification.